Audit Delay Phenomenon in Companies Listed on the Indonesia Stock Exchange - Fitria, Lustri (Journal Research of Social Science, Economics, and Management, 2024)
This study was conducted to examine the effect of financial distress, company size and audit committee on audit delay. This study uses companies that are delayed in submitting audited financial statements listed on the Indonesia Stock Exchange for the 2019-2021 period using the purposive sampling method. The selection of samples from 205 companies listed on the Indonesia Stock Exchange in 2019-2021 resulted in 116 acceptable samples. The data analysis method used in the study was Multiple Linear Regression Analysis with Eviews 12 with a significance level of 5%. The results of this study show that: (1) Financial distress does not affect audit delay, (2) Company size has a significant and positive effect on audit delay, (3) Audit committee does not affect audit delay.